Functional MRI of Handwriting Tasks: A Study of Healthy Young Adults Interacting with a Novel Touch-Sensitive Tablet - Karimpoor, Mahta; Churchill, Nathan W.; Tam, Fred; Fischer, Corinne E.; Schweizer, Tom A.; Graham, Simon J. (Frontiers in Human Neuroscience, 2018)
Handwriting is a complex human activity that engages a blend of cognitive and visual motor skills. Current understanding of the neural correlates of handwriting has largely come from lesion studies of patients with impaired handwriting. Task-based fMRI studies would be useful to supplement this work. To address concerns over ecological validity, previously we developed a fMRI-compatible, computerized tablet system for writing and drawing including visual feedback of hand position and an augmented reality display. The purpose of the present work is to use the tablet system in proof-of-concept to characterize brain activity associated with clinically-relevant handwriting tasks, originally developed to characterize handwriting impairments in Alzheimer’s disease patients. As a prelude to undertaking fMRI studies of patients, imaging was performed of twelve young healthy subjects who copied sentences, phone numbers, and grocery lists using the fMRI-compatible tablet. Activation maps for all handwriting tasks consisted of a distributed network of regions in reasonable agreement with previous studies of handwriting performance. In addition, differences in brain activity were observed between the test subcomponents consistent with different demands of neural processing for successful task performance, as identified by investigating three quantitative behavioural metrics (writing speed, stylus contact force and stylus in air time). This study provides baseline behavioural and brain activity results for fMRI studies that adopt this handwriting test to characterize patients with brain impairments.